PENGEMBANGAN PERANGKAT PEMBELAJARAN BERDASARKAN MODEL 4-D PADA MATERI GETARAN GELOMBANG DAN BUNYI DALAM MENINGKATKAN PEMAHAMAN KONSEP SISWA SMP NEGERI 6 PALU - Ernawati, Ernawati (JSTT, 2014)
One of the reason for poor students understanding of physics concepts is less availability of particular books supporting the learning activities and the lack of development of learning tools expecially the material vibrations, waves and sound. This research is a development study with the limited test that aims to develop the instructional materials in natural science physics of the topic vibrations waves and sound, including teaching materials, students worksheet, and lesson plan. The subject of this research was students at VIIIA class of SMP Negeri 6 Palu with 40 students. There were four steps of the development of this model: (l) defining, including student analysis, concept analysis, task analysis, and specification indicator of learning outcomes; (2) designing, containing media selection, the selection of format, and the early design of instructional materials; (3) developing, dealing with expert validation, simulation, and revision; and (4) distributing. The strength of instructional materials compiled systematically could improve the studentsâ€™ concept understanding and make the teaching-learning process in the classroom easier. The effectiveness of the instructional materials obtained by t-test which wasÂ tcounted (5.967) > ttable (1.664). Based on the result of data analysis and t test, also the test result of concept understanding, it can be concluded that the product of the instructional materials development of Natural Science Physics with the topic of vibration waves and sound by using 4-D development model at SMP Negeri 6 Palu, which was valid and effective as teaching material for students, student worksheet, and lesson plan have been produced.